PENGARUH CORPORATE GOVERNANCE PADA CORPORATE SOCIAL RESPONSIBILITY DAN EARNING MANAGEMENT TERHADAP NILAI PERUSAHAAN - Achmad Subari, 08.05.52.0108; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2012)
This research to analyze the effect of corporate governance on CSR and earning management of the corporate value after the issuance of Law No. 40 Year 2007 regarding Limited Liability Company in manufacturing companies on the Stock Exchange with the perspective of agency theory and expectancy theory. Appropriate agency to resolve the conflict theory and agency theory expectations are expecting a certain strength to enhance shareholder value.The research proved that corporate governance has no effect on corporate value, CSR affects corporate value, earning management doesnât affect on corporate value, corporate governance proved not as moderating variableon CSR and corporate value, corporate governance proved to be a moderating variable on earning management and corporate value. InÂ this study supports the agency theory and expectacy theory to enhance shareholder value.Keywords: Corporate Governance, Corporate Social Responsibility, Earning Management, Corporate Value